Dynamics of Response to Asynapsis and Meiotic Silencing in Spermatocytes from Robertsonian Translocation Carriers - Naumova, Anna K. (Public Library of Science, 2013)
Failure of homologous synapsis during meiotic prophase triggers transcriptional repression. Asynapsis of the X and Y chromosomes and their consequent silencing is essential for spermatogenesis. However, asynapsis of portions of autosomes in heterozygous translocation carriers may be detrimental for meiotic progression. In fact, a wide range of phenotypic outcomes from meiotic arrest to normal spermatogenesis have been described and the causes of such a variation remain elusive. To better understand the consequences of asynapsis in male carriers of Robertsonian translocations, we focused on the dynamics of recruitment of markers of asynapsis and meiotic silencing at unsynapsed autosomal trivalents in the spermatocytes of Robertsonian translocation carrier mice. Here we report that the enrichment of breast cancer 1 (BRCA1) and histone γH2AX at unsynapsed trivalents declines during the pachytene stage of meiosis and differs from that observed in the sex body. Furthermore, histone variant H3.3S31, which associates with the sex chromosomes in metaphase I/anaphase I spermatocytes, localizes to autosomes in 12% and 31% of nuclei from carriers of one and three translocations, respectively. These data suggest that the proportion of spermatocytes with markers of meiotic silencing of unsynapsed chromatin (MSUC) at trivalents depends on both, the stage of meiosis and the number of translocations. This may explain some of the variability in phenotypic outcomes associated with Robertsonian translocations. In addition our data suggest that the dynamics of response to asynapsis in Robertsonian translocations differs from the response to sex chromosomal asynapsis in the male germ line.